2018
DOI: 10.1049/iet-stg.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ultra‐fast charging stations within the power grids of smart cities: a review

Abstract: Plug-In Electric Vehicles (PEV) have become a key factor driving towards smart cities, which allow for higher energy efficiency and lower environmental impact across urban sectors. Industry vision for future PEV includes the ability to recharge a vehicle at a speed comparable to traditional gas refueling, i.e., less than 3 minutes per vehicle. Such a technology, referred to as Ultra-Fast Charging (UFC), has drawn much interest from research and industry. The large power density, impulsive, and stochastic loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 84 publications
(177 reference statements)
0
56
0
Order By: Relevance
“…4b and 5b shows the evolution of probability vectorv t , which converges to a binary vector corresponding to the optimal solution. Therefore, the optimal locations to place FCS for N F CS = 5 and N F CS = 10 are X = [8,9,13,20,22] and X = [3,4,7,8,9,12,13,20,22,23], respectively.…”
Section: B Location Planning Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b and 5b shows the evolution of probability vectorv t , which converges to a binary vector corresponding to the optimal solution. Therefore, the optimal locations to place FCS for N F CS = 5 and N F CS = 10 are X = [8,9,13,20,22] and X = [3,4,7,8,9,12,13,20,22,23], respectively.…”
Section: B Location Planning Resultsmentioning
confidence: 99%
“…As an unconventional type of electric load, PEV consumes a large amount of power in a fast and discrete manner, which far exceeds the peak power demand for an average household in the U.S [2]. In continuing towards the goal of resembling traditional refueling stations, multiple charge ports per station are built, bringing total power capacity in a Fast Charging Station (FCS) to Megawatt level [3]. Prior works have shown that the impulsive characteristics of PEV charging load, especially when aggregated at the FCS, will result in negative impacts on the power grid, including disruptively varying voltage profiles along the feeder and lifetime depreciation of critical grid assets [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, minimizing the total operation cost of the whole system is regarded as the objective function. The total cost can be described by equations (4)- (7). Since there are many EVs in each microgrid, it is not impractical to optimize the charging and discharging powers of every EV, nor is it necessary.…”
Section: Objective Functionmentioning
confidence: 99%
“…Most research has discussed the issue from the aspect of economic dispatching. The majority of the studies elaborated the optimal charging management of EVs [6,7]. However, as a kind of storage units, EVs can also discharge to the main grid or microgrid, providing a vehicle-to-grid (V2G) service to participate into the operation of the power systems [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although this option creates a lesser burden for the EV user in terms of charging time, the challenge remains to limit the impact of charging rates >50 kW have on the cycle-life of the respective battery packs. Moreover, fast-chargers put a substantial strain on the available power grid [42,43] , if they are not coupled to a local storage system, consisting of second-life batteries or supercapacitors that are charged when power demand is low. For these reasons, a concept of in-life modularity is proposed in this paper, consisting of a range-extender trailer that can be connected to an EV.…”
mentioning
confidence: 99%